Rozwój ekonomiczny regionów w Polsce a efektywność zawodowa kobiet - Knychała, Krystyna (Wydział Prawa i Administracji UAM, 1978)
The subject of this paper is the determination of the two groups of interdependance. The first one concerns the determination of the relation between apportionment of female staff among the areas of economic activity and the economic development of Poland in the post-war period. The second one concerns the relation between the range of female professional activity in the economic spheres and the place of particular regions in the level of economic development. Statistical methods (taxonomic method of similarity and multiple correlation calculation among them) have been used in the paper. As the result of the analysis, it has been established that the range of female professional activity in the particular spheres in the post-war period in Poland formed a function of economic development determining the scale of the demand for female labour force in industry. The development of industry in connection with the second zone and its underdevelopment in the case of the first and third area determined the high female professional activity in particular regions. This interdependance in the process of time loses its value according to the universal economic causality.
Economic Development of Regions in Poland and the Female Professional Activity